Epilepsia Partialis Continua as a Symptom of Alcohol Withdrawal in a Type 2 Diabetic Patient. - Kumar, Chandan; Athwal, Pal Satyajit Singh; Gulati, Akanksha; Khan, Yaqoob; Singh, Yuvraj (Asian Journal of Medical Research, 2019)
Epilepsia partialis continua is a rare form of focal epilepsy or focal status epilepticus which mostly involves motor component. It leads to arrhythmic muscle jerks for a prolonged period of time. It can present as a single episode or multiple repetitive episodes. There are multiple etiological factors including vascular lesions and tumors. Presenting as alcohol withdrawal in a type 2 Diabetic patient makes it a rare phenomenon. We report a case of 55-year-old male with Epilepsia partialis continua after alcohol abstinence. Familiarity and diagnosis of this rare event is important because the treatment depends on the underlying etiology.